Economic inequalities and the level of decentralization in European countries: Cluster analysis - Šárka Laboutková; Pavla Bednářová; Vladimíra Hovorková Valentová (Comparative Economic Research. Central and Eastern Europe, 2016)
This submitted article identifies relations between the degree of decentralization and economic imbalances on the basis of a cluster (exploratory) analysis. Two indicators have been chosen for measuring economic inequalities: an indicator of dispersion of regional GDP per capita as representative of the performance imbalances within countries (it measures the economic development gap among regions in European countries); and a multidimensional inequality-adjusted human development index as representative of inequalities in the distribution of wealth in the countries. Decentralization is measured by means of a decentralization index, which contains both quantitative and qualitative components. Although groups of countries characterised by a high degree of decentralization do not necessarily show the lowest degrees of economic imbalances, it is however possible to conclude that the countries in groups with a higher degree of decentralization are among those countries with more favourable values of the economic imbalances indicators monitored. As a part of the research, two clusters of countries were identified which are identical in their degree of decentralization, but differ in the results connected with economic imbalances. The differences are caused by different institutional qualities in the two groups.
Keywords: 330; cluster analysis; decentralization; economic development; human development; inequality; regional disparities